2014
DOI: 10.1287/orsc.2013.0875
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Be Edison: Inventors, Organizations, and Breakthrough Inventions

Abstract: This study examines whether inventors’ past stock of inventions affects the rate at which they produce technological breakthroughs, as well as the role of organizational contingencies in moderating this effect. The breakthrough rate depends on the rate at which an inventor generates inventions and the probability that each of these inventions is a breakthrough. We argue that inventors with larger patent records generate a higher rate of inventions, but the single inventions that they generate each have a lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…We also suggest that it may be advantageous for founders to hire star inventors with prior experience in working in new ventures as opposed to older established organizations. Our findings align with prior work that has shown that firms may experience suboptimal results when they organize their innovation teams such that experienced inventors have to work under managerial supervision and guidance (Conti et al, ) or when the presence of stars fosters an over‐reliance on their contributions resulting in inhibiting non‐star teammates' knowledge acquisition (Li, Li, Li, & Li, in‐press).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We also suggest that it may be advantageous for founders to hire star inventors with prior experience in working in new ventures as opposed to older established organizations. Our findings align with prior work that has shown that firms may experience suboptimal results when they organize their innovation teams such that experienced inventors have to work under managerial supervision and guidance (Conti et al, ) or when the presence of stars fosters an over‐reliance on their contributions resulting in inhibiting non‐star teammates' knowledge acquisition (Li, Li, Li, & Li, in‐press).…”
Section: Discussionsupporting
confidence: 88%
“…Second, we extend recent research on the effects of informal hierarchy among group members (He & Huang, ; Kilduff et al, ) by showing how ambiguous hierarchies may undermine the ability of the new venture to innovate successfully. Finally, our research contributes to and extends understanding of how an important aspect of organizational design, the makeup of the innovation team (cf., Conti, Gambardella, & Mariani, ), has important consequences for the venture's subsequent success in introducing new products.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our results complement the evidence provided by recent studies in the management tradition that look at the sources of innovative breakthroughs mainly at the individual level. While the probability of achieving a breakthrough may be related to inventors' past experience and ability (Conti et al 2010) and/or to the organizational setting in which the research activity takes place (Jeppesen and Lakhani 2010), industry characteristics seem also to play an important role and ought to be considered when carrying out firm level studies. Finally, our results bear also some policy implications.…”
Section: Discussionmentioning
confidence: 99%
“…The topic of this special issue is breakthrough innovations, defined as high‐impact innovations (Conti, Gambardella, and Mariani, ; Kaplan and Vakili, ; Phene et al, ) or products “that create entirely new markets or radically change existing ones” (Colombo et al, ). It is typically argued that producing breakthrough innovation involves re‐combination of distant and diverse knowledge bases (e.g., Cassiman et al, ; Kaplan and Vakili, ) and the ability to explore complex issues with a deep‐dive into a specific arena (e.g., Padgett and Powell, ; Weisberg, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The two modes of organizing—external and internal knowledge development—have different implications for how (scarce) resources are allocated toward progressing products under development to market (e.g., Conti et al, ). The internal mode is associated with a large firm mentality and relatively slow internal knowledge sharing.…”
Section: Theoretical Frameworkmentioning
confidence: 99%